The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0102-76382008000300023
|View full text |Cite
|
Sign up to set email alerts
|

Tamponamento cardíaco em dois recém-nascidos causado por cateter umbilical

Abstract: Tamponamento cardíaco em dois recém-nascidos causado por cateter umbilical Cardiac tamponade caused by central venous catheter in two newborns AbstractCardiac tamponade secondary to the use of central venous catheter is a rare complication; however, it is potentially reversible when it is caught in time. We report two cases of cardiac tamponade that was diagnosed using a transthoracic echocardiography, followed by urgent pericardiocentesis and surgical pericardial drainage as a complication from umbilical veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
7
0
5
Order By: Relevance
“…However, the cannulation for a central venous catheter (CVC) can place patients at risk, with fatal complications such as arrhythmia [3], pneumothorax [4], inadvertent arterial puncture [5], hemothorax [6] or cardiac tamponade [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…However, the cannulation for a central venous catheter (CVC) can place patients at risk, with fatal complications such as arrhythmia [3], pneumothorax [4], inadvertent arterial puncture [5], hemothorax [6] or cardiac tamponade [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have used ultrasound examination to demonstrate the incorrect positioning of catheters that the radiological examination showed to be ideally located [10][11][12] .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that there is no difference in the risk of death from cardiac tamponade related to PICC for factors such as gestational age and weight 16,17 . Regarding general mortality among newborns with this condition, Nowlen et al 16 12,20,21 , reviews or meta-analyzes [15][16][17] . In the last 13 years, there have been original studies evaluating the complications related to the use of PICC 7,8,19,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This complication occurs in up to 3% of the newborn cases with central venous access. [ 1 ] We report a case of cardiac tamponade following central venous cannulation that was diagnosed using a transthoracic echocardiography, managed by urgent surgical pericardial drainage. Complications with central line insertion in neonates occur most likely with guide wire aided insertion, with blind needling of a chest vein and with dilators.…”
Section: Introductionmentioning
confidence: 99%